The evaluation of upper leg traction in lateral position for pediatric caudal block - Seyedhejazi, Mahin (Medknow Publications, 2011)
PURPOSE: A well-functioning caudal block is an excellent adjunct to general anesthesia, but misplaced injection results in poor analgesia as well as possibility of serious morbidity. Therefore, the purpose of this study was to evaluate the effectiveness of leg traction on success rate of caudal block in lateral position in children. METHODS: Two hundred children, age 2 months to 6 years, ASA I and II, who underwent lower abdominal surgeries were randomized in prospective controlled clinical trial study in two groups. After induction of General anesthesia, the caudal block was performed in the lateral position with upper leg traction (L-T-) or with the standard position (S-P) (leg flexed 90°). Hemodynamicchanges, movement of lower extremity in response to surgical stimulus were evaluated. RESULTS: There was no significant difference in caudal block's success rate between two groups at first attempt (P=0.25). In group (S-P) the procedure was successful in 60% of cases at first attempt, 25% at second,10% at third attempt and 5% failure of caudal block, whereas in the first group it was 75%, 20%, 1% and 4% of cases respectively. There were no significant differences in heart rate and blood pressure changes between two groups (P>0.05). CONCLUSION: The success rate of pediatric caudal block in upper leg traction did not differ from that of the standard position.